(untitled) (American Journal of Business Management, Economics and Banking, 2023)
The aims of study to introduce the importance of incoming tourism spending and its impact on the economies of the country concerned with receiving tourists and its impact on macroeconomic indicators, especially the average Iraqi per capita GDP, which developed according to the years of study 2004 to 2020 likely for the reasons of security and political instability, economic reasons and even health reasons such as the Corona pandemic, which harmed the world and Iraq, and the researchers adopted a descriptive analytical approach to study the reality of the relationship between tourism spending and the average Iraqi per capita GDP, which Reach the fluctuation of the results of the relationship due to the factors determining it.